ANALISIS KONTEN INSTAGRAM @pariwisata.padang DESTINASI WISATA ALAM DI KOTA PADANG, SUMATRA BARAT DALAM PERSPEKTIF KOMUNIKASI PARIWISATA - Radha Yasmin; Muaz Tanjung (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2026)
This study aims to analyze tourism communication on the official Instagram account of the Padang City Tourism Office (@pariwisata.padang) in promoting natural tourism destinations. From a tourism communication perspective, this research examines how messages are constructed through visuals, captions, hashtags, and audience interaction. A qualitative approach with content analysis techniques was applied to Instagram posts from March to June 2025. Data collection involved documentation and non-participant observation of visual aesthetics, storytelling narratives, and audience engagement. The results indicate that @pariwisata.padang effectively utilizes digital elements to build a positive destination image. However, the communication pattern remains predominantly one-way, leading to sub-optimal interactivity. Identified communication barriers include low two-way engagement, lack of Call to Action (CTA) strategies, and ineffective digital distribution. This study concludes that while Instagram is a vital tool for establishing destination image, strengthening interactive strategies is essential to enhance active participation among digital tourists.